Counselor Responsibility in Confronting the Neglected Counselor Label - Gusman Lesmana; Widya Anggriani Putri; Sri Rezeki (Yayasan Zia Salsabila, 2023)
This research aims to reveal how the responsibility of guidance and counseling teachers in confronting the neglected guidance and counseling label. The type of research used in this research is literature, where the author uses a descriptive normative research approach with more emphasis on the power of data analysis from existing data sources. Researchers to collect information that is relevant to the topic or problem that will be or is being researched. The results of this research show that guidance and counseling teachers play an important role in students' success in undergoing the education process at school. The duties of a guidance counselor include understanding and observing student behavior as well as providing counseling services that help students overcome the various problems they face. Not only teaching and providing counseling to students, guidance counselors also have many responsibilities that must be carried out in accordance with the counselor's professionalism. Basically, guidance and counseling teachers are needed to meet the social and psychological needs of children at school. BK teachers are seen as teachers who solve the problems of undisciplined children. In fact, guidance and counseling teachers have a big role in shaping the character of students, not just dealing with the problem of naughty children, but their role is very crucial in guiding students to be successful in learning.